SOCIAL RESPONSIBILITY OF HIGHER EDUCATION INSTITUTIONS IN THE CONTEXT OF HARMONIZATION OF COOPERATION AND SUSTAINABLE DEVELOPMENT - Verbovska, Lesya; Боднар, Галина Федорівна (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2024)
The article proves that Ukrainian institutions of higher education in their activities should pay more attention to social responsibility, to form harmonized relations with students, stakeholders and to form relations in society to harmonized relations, being a socially responsible individual. It is substantiated that social responsibility and sustainable management are timely in today’s changing external environment, therefore it should develop through the creation of initiatives by institutions of higher education, which in turn should serve as a platform for training a socially responsible specialist. It has been proven that under "social responsibility" and "harmonization" of Ukrainian higher education institutions, it is necessary to understand complex cooperation, and in the strategy to write down the mission, vision, goals, prospects for development, readiness to share experience and provide reliable and high-quality knowledge, which will create the added value of the institution higher education through socially responsible initiatives in the context of sustainable development goals. Within the framework of the study, an analysis of the main factors of social responsibility was carried out; the rating of the introduction of social responsibility factors into educational programs is presented; examples of initiatives that contribute to the training of socially responsible specialists are presented, through which harmonized relationships are formed and mutual responsibility can be realized. It has been demonstrated that the social responsibility of a higher education institution is formed through dynamism, flexibility, meeting the needs and interests of stakeholders through learning to be socially responsible, active, without disturbing various spheres of influence, and without jeopardizing the main functions of the higher education institution. Proposals are presented on the possibilities of revising educational programs that will help shape the main initiatives, relevant policies and practices for sustainable development; develop initiatives for sharing knowledge, making socially responsible decisions, creating socially responsible initiatives. It has been proven that Ukrainian institutions of higher education, guided by international experience, should develop initiatives to promote economic, technological and cultural development, in order to strengthen social responsibility and harmonize relations.